Legal Protection Efforts and Policies to Combat Deepfake Porn Crimes with Artificial Intelligence (AI) in Indonesia - Ocktave Ferdinal; Herman Bakir (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. The rapid development of artificial intelligence (AI)-based technologies, including deepfake, has introduced new challenges to the legal system. Deepfake porn, which manipulates digital content to create fake explicit materials, threatens privacy, dignity, and personal reputation. In Indonesia, existing laws related to pornography and electronic information are insufficient to address these crimes effectively, leaving victims vulnerable. Purpose. This study aims to analyze the legal gaps in addressing AI-based cybercrimes, especially deepfake porn, and propose legal policies to provide better protection for individuals while balancing technological innovation. Method. A qualitative approach was employed, combining doctrinal legal research with case analysis. Legal frameworks, including Indonesia’s Law on Pornography and the Electronic Information and Transactions (ITE) Law, were reviewed alongside global legal precedents on AI misuse. Results. The study reveals that existing laws are outdated in handling AI-driven crimes. There is an urgent need for specific regulations addressing the misuse of AI, particularly in creating and distributing deepfake content. Effective enforcement mechanisms and victim support systems are also lacking. Conclusion. To combat deepfake porn crimes, Indonesia must establish specific legal frameworks regulating AI misuse and ensuring accountability. Clear definitions, strict penalties, and victim protection measures should be integral to these policies.